Character Education Practices At Al Azhar Islamic School Bumi Serpong Damai@Metland - Imamur Risqi; Nur Wahyu Rochmadi; Suko Wiyono (Eduvest - Journal of Universal Studies, 2024)
Character education in schools is very necessary because character education is the core of education itself. Building character, it can't be done tomorrow. Therefore, character-based Character education in schools is very necessary, because character education is the main thing of education. This research was conducted to examine the practice of character education in schools. The purpose of this study is to describe the implementation of character education at Al Azhar BSD@Metland Islamic School in terms of 1) character education objectives; and 2) character education strategies. This research uses case study research method to answer these questions. The researcher acts as the main instrument and collects data by means of observation, in-depth interviews, and documentation. The research data came from the implementation of character education at Al Azhar BSD@Metland Islamic School. To ensure the legality of the data, this research applies triangulation of data sources, theories, and methodologies. The findings of this study imply that overall, the implementation of character education at Al Azhar BSD@Metland Islamic School has been carried out through habituation programs or routine activities applied by the school to its students, including character building activities in the form of teaching and learning activities carried out by educators with competencies in accordance with their fields and carried out regularly and on schedule. The policy implemented to fulfill this goal is to carry out 8 religious policies that have been effectively implemented at Al Azhar BSD@Metland Islamic School.